Vital Capacity in Different Body Postures among Medical Students - Ghimire, Nisha; Mukhopadhyay, Soumitra (Medical Journal of Eastern Nepal, 2023)
Background: Cross legged sitting posture (sukhasana, yogic) is normal sitting posture in India, Nepal and some neighboring countries. This posture is also claimed to deepen breath. However, not many studies have been documented to observe if there is any difference in vital capacity (VC) of lungs in standing, sitting erect posture in chair, and sitting erect in crossed legged posture. So, our aim is to compare the vital capacity in standing, sitting erect posture in chair, and crossed legged sitting posture.Methods: Forty medical and paramedical students (20 males and 20 females) of Nobel medical college were selected for the study. After selecting the students as per selection criteria, vital capacity was measured with spirometer in standing, sitting erect on chair (palms facing up and down) and sitting erect in crossed legged posture (palms facing up and down). One way ANOVA followed by post hoc analysis was done to compare the vital capacity among different postures. Data were expressed as Mean ± SD. p value